Upaya Peningkatan Kapasitas Perempuan Desa Karang Intan melalui Pelatihan Komunikasi Efektif - Agianto Agianto; Ghina Ghaida Mutmainah; M. Gilang Syahrial Putra; Dhifa Azzahri Putri; Salsabila Putri Anjali (JURNAL SUAKA INSAN MENGABDI (JSIM), 2025)
Karang Intan Village has a big number of human resource potential, one of them is women who are active in organizations. However, their public speaking skills have not been utilized optimally, and be limited their contribution and participation in village organizations. This activity aimed to improve women's communication skills through speaking training in public area. There were 13 village women consisting of cadres, housewives and PKK women who were involved in this training using a purposive sampling technique. Implementation of activities consists of three stages, namely preparation, implementation, and evaluation. Preparation phase includes coordination, determining material, as well as preparing the pre-test and post-test instruments. Implementation phase is the delivery of material and training sessions, while evaluation is carried out with post-tests and mentoring. The data analysis used the Wilcoxon Signed Rank Test (a < 0.05). The analysis results showed that there was no significant difference ??before and after training (p=0.157). Training is able to improve village women's communication skills in more intense stages and also improve leadership in organizations.